2011
DOI: 10.1039/c1ob05871a
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of copillar[5]arenes and their host–guest properties with dibromoalkanes

Abstract: An efficient method for the synthesis of copillar[5]arenes was developed with FeCl(3) as catalyst and different 1,4-dialkoxybenzenes and paraformaldehyde as reactants (yields: 50-85%). The host-guest property of (co)pillar[5]arenes and terminal dibromoalkanes was investigated by (1)H NMR measurements and an X-ray study. The complexation behavior of the copillar[5]arenes can be tuned by changing the substituents on the host. A complete complexation selectivity was found between pillar[5]- and pillar[6]arenes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(38 citation statements)
references
References 19 publications
0
36
0
2
Order By: Relevance
“…The scope of pillararenes as hosts can be expanded by substituting the rim alkoxy positions with a desired group; either by cocyclisation of a functionalised monomeric subunit with 1,4-dimethoxybenzene [21,22]; by dealkylation and further reaction of the already formed macrocycle [23][24][25]; or by preorienting the cyclisation reaction with a 2,5-substituted benzyl alcohol [26,27], the latter affording ''rim-differentiated" pillararenes where each rim is pre-functionalised with a desired group. The chemistry of these fascinating molecules has recently been extended to a new family of tiara [5]arenes that exhibit more conformational flexibility [28].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of pillararenes as hosts can be expanded by substituting the rim alkoxy positions with a desired group; either by cocyclisation of a functionalised monomeric subunit with 1,4-dimethoxybenzene [21,22]; by dealkylation and further reaction of the already formed macrocycle [23][24][25]; or by preorienting the cyclisation reaction with a 2,5-substituted benzyl alcohol [26,27], the latter affording ''rim-differentiated" pillararenes where each rim is pre-functionalised with a desired group. The chemistry of these fascinating molecules has recently been extended to a new family of tiara [5]arenes that exhibit more conformational flexibility [28].…”
Section: Introductionmentioning
confidence: 99%
“…而化合物 36 [21] 则可以同正己烷形成包合物, 推动这种主客体相 互作用的是 C-H…π 相互作用, 尽管它是一种最弱的 氢键. 另外, 在最新的报道中, 柱芳烃化合物还可以有 效识别二溴代烷烃类化合物 [27] .…”
Section: 先成环后修饰unclassified
“…However, very little is known about the complexation selectivity for non-symmetrical pillar [5]arenes, especially the monofunctionalized copillar [5]arene, [30] although this type of structure has become the central topic of many studies because of their easy functionalization and different self-assembly behavior. [31,32] In previous work, [30,[33][34][35][36][37][38][39][40] we have known that pil-lar [5]arenes or biphen[n]arenes, which were first reported by Li et al [41] in 2015, showed good binding properties to the symmetrical guests such as the linear α,ω-dihaloalkane, α,ω-dihydroxyalkane and α,ω-diaminoalkane by the two interactions of the cavity. In contrast, the unsymmetrical guests possessing one binding site always showed weak or no interaction.…”
Section: Introductionmentioning
confidence: 98%